Is Longitudinal Division in Rod-Shaped Bacteria a Matter of Swapping Axis? - den Blaauwen, Tanneke (Frontiers in Microbiology, 2018)
The morphology of bacterial species shows a wealth of variation from star-shaped to spherical and rod- to spiral-shaped, to mention a few. Their mode of growth and division is also very diverse and flexible ranging from polar growth and lateral surface increase to midcell expansion and from perpendicular to longitudinal asymmetric division. Gammaproteobacterial rod-shaped species such as Escherchia coli divide perpendicularly and grow in length, whereas the genetically very similar rod-shaped symbiotic Thiosymbion divide longitudinally, and some species even divide asynchronously while growing in width. The ovococcal Streptococcus pneumoniae also lengthens and divides perpendicularly, yet it is genetically very different from E. coli. Are these differences as dramatic as is suggested by visual inspection, or can they all be achieved by subtle variation in the regulation of the same protein complexes that synthesize the cell envelope? Most bacteria rely on the cytoskeletal polymer FtsZ to organize cell division, but only a subset of species use the actin homologue MreB for length growth, although some of them are morphologically not that different. Poles are usually negative determinant for cell division. Curved cell poles can be inert or active with respect to peptidoglycan synthesis, can localize chemotaxis and other sensing proteins or other bacterial equipment, such as pili, depending on the species. But what is actually the definition of a pole? This review discusses the possible common denominators for growth and division of distinct and similar bacterial species.